Programming of stress-related behavior and epigenetic neural gene regulation in mice offspring through maternal exposure to predator odor - St-Cyr, Sophie; McGowan, Patrick O. (Frontiers in Behavioral Neuroscience, 2015)
Perinatal stress mediated through the mother can lead to long-term alterations in stress-related phenotypes in offspring. The capacity for adaptation to adversity in early life depends in part of the life history of the animal. This study was designed to examine the behavioral and neural response in adult offspring to prenatal exposure to predator odor: an ethologically-relevant psychological stressor. Pregnant mice were exposed daily to predator odors or distilled water control over the second half of the pregnancy. Predator odor exposure lead to a transient decrease in maternal care in the mothers. As adults, the offspring of predator odor-exposed mothers showed increased anti-predator behavior and predator-odor induced decrease in activity, in female offspring, an increased corticosterone response to predator odor exposure. We found a highly specific response among stress-related genes within limbic brain regions. Transcript abundance of CRHR1 (Corticotropin-releasing hormone receptor 1) was elevated in the amygdala in female offspring of predator odor-exposed dams. In the hippocampus of adult female offspring, decreased BDNF (Brain-derived neurotrophic factor) gene expression was correlated with a site-specific decrease in DNA methylation in the Bdnf exon IV, indicating the potential contribution of this epigenetic mechanism to maternal programming by prenatal predator odor exposure. These data indicate that prenatal predator odor exposure alone is sufficient to induce an altered stress-related phenotype in adulthood, with implications for anti-predator behavior in offspring.